Description of novel microsatellite loci in the Neotropical fish Prochilodus argenteus and cross-amplification in P. costatus and P. lineatus - Barbosa,Anna C.D.R. (2008)
Prochilodus is one of the most important fish resources of South America, in addition to the important role it plays in nutrient cycling of Neotropical rivers. In the present study, we describe the isolation and characterization of nine novel microsatellite loci in Prochilodus argenteus. The number of alleles per polymorphic locus varied from 5 (Par76) to 21 (Par85), revealing a total of 116 alleles. The values of observed and expected heterozygosities ranged from 0.629 (Par69) to 0.926 (Par85 and Par86) and from 0.643 (Par66) to 0.931 (Par80), respectively. Furthermore, the ability of these and other previously described microsatellite markers to amplify orthologous loci was tested in two related species, Prochilodus costatus and Prochilodus lineatus. These loci will be useful for studies of population genetic structure in this group of fishes, and in aiding future genetic mapping studies of P. argenteus.